Cine y Teorías Criminológicas - Norberto, Hernández Jiménez (2016)
This paper aims to show how both (i) dogmatic categories of criminal law and (ii) criminological theories can be analyzed through movies. These two issues, which sometimes become difficult for students and the general public, can be simplified with the use of this audiovisual tool. In fact, movies help obtain greater academic openness and discussion